A Study of Employee Perceptions About Performance Appraisal at Transnet Engineering, South Africa - Worku, Zeleke (Journal of Applied Business Research, 2019)
Transnet Engineering is a division of Transnet, which is a key South African state owned enterprise that is responsible for providing railroad, freight and logistics services to South African and international business enterprises. Transnet Engineering is located at Koedoespoort, just outside Pretoria, South Africa. This manuscript is a result of data gathered from 198 employees of Transnet Engineering as part of an attempt made by the company to describe and quantify the perception held by employees of Transnet Engineering on the degree to which the performance of appraisal system used by the company for performance appraisal was suitable enough for its intended purpose. The perception of employees was measured by using a benchmark defined by Pichler (2012) in which similar measurements were made under near-identical circumstances. All measurements were taken based on a standardised, validated and pre-tested instrument. Pearson’s two-by-two chi-squared tests of associations, discriminant analysis and logit regression were used for analyses. The study found that about 63% of participants were happy with the performance appraisal system used by the company, whereas about 37% of participants held a negative perception. The results confirmed that the perception of employees about the performance appraisal system used at Transnet Engineering was affected by the perception of employees on fairness, and the assessment of performance of employees based on key performance indicators. Findings obtained from the study are quite relevant and valuable to all other South African state owned enterprises.
Keywords: business; research; Transnet Engineering; Performance Appraisal; Perception; Discriminant Analysis